2020
DOI: 10.21037/gs.2020.03.20
|View full text |Cite
|
Sign up to set email alerts
|

The impact of radiation on lymphedema: a review of the literature

Abstract: Radiation therapy (RT) is a common adjunct therapy in oncology. However, it carries a significant risk of lymphedema when utilized in some anatomic locations. Recent studies have provided insight into lymphedema pathophysiology, diagnostic techniques, and RT. This review will examine the role of RT in upper and lower extremity lymphedema. Radiation's role in increasing the risk of lymphedema through decreased lymphatic proliferation potential, interstitial fibrosis compressing lymphatic vessels, and mechanical… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
46
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 54 publications
(47 citation statements)
references
References 64 publications
0
46
1
Order By: Relevance
“…Lymphedema is a chronic, potentially progressive disorder which is characterized by the pathological accumulation of lymphatic fluid and fibrosis of subcutaneous tissue somewhere in the body. In BC survivors, this tissue is in the ipsilateral arm of BC and most often appears after axillary lymph node dissection and axillary radiotherapy [ 7 , 8 ]. This secondary lymphedema often causes functional problems, adversely affects quality of life, and may be accompanied by recurrent infections [ 9 ].…”
Section: Introductionmentioning
confidence: 99%
“…Lymphedema is a chronic, potentially progressive disorder which is characterized by the pathological accumulation of lymphatic fluid and fibrosis of subcutaneous tissue somewhere in the body. In BC survivors, this tissue is in the ipsilateral arm of BC and most often appears after axillary lymph node dissection and axillary radiotherapy [ 7 , 8 ]. This secondary lymphedema often causes functional problems, adversely affects quality of life, and may be accompanied by recurrent infections [ 9 ].…”
Section: Introductionmentioning
confidence: 99%
“…Our data suggest that this decline might be moderated with HIT, particularly in regard to depression and anxiety outcomes, activity and function 87 and activities of daily living 88 . Most of the negative side effects of cancer and its treatments are related to reduced physical functioning, reduced mobility due to surgery or chemotherapy 89 , lymphedema 90 , negative body composition changes as sarcopenia 91 , or osteoporosis 92 . Providing opportunities to increase independence through HIT is highly important since more than half of all cancer patients develop a mobility disability because of the disease and its treatments' adverse side-effects 93 .…”
Section: Discussionmentioning
confidence: 99%
“…Bar Ad et al (2010) reported that 16% of all patients undergoing treatment with a combination of lymph node resection and radiation therapy developed clinical signs of lymphedema [ 56 ], whereas radiation therapy led to the highest incidences at 31% [ 55 ]. Radiation therapy can lead to the reduction of proliferative potential of the lymphatic tissue, fibrosis of the lymph nodes or to a mechanical insufficiency of the lymphatic vasculature [ 57 ]. Additional co-factors in the development of secondary lymphedema can be congestive heart failure or renal diseases [ 58 ].…”
Section: Overview Of Lymphedemamentioning
confidence: 99%